Immunosuppressive Therapy Improves Both Short- and Long-Term Prognosis in Patients With Virus-Negative Nonfulminant Inflammatory Cardiomyopathy. (February 2018) - Merken, Jort; Hazebroek, Mark; Van Paassen, Pieter; Verdonschot, Job; Van Empel, Vanessa; Knackstedt, Christian; Abdul Hamid, Myrurgia; Seiler, Michael; Kolb, Julian; Hoermann, Philipp; Ensinger, Christian; Brunner-La Rocca, Hans-Peter; et al.
Abstract : Background: Inflammatory cardiomyopathy (infl-CMP) is characterized by increased cardiac inflammation in the absence of viruses, ischemia, valvular disease, or other apparent causes. Studies addressing the efficacy of immunosuppressive therapy in patients with infl-CMP are sparse. This study retrospectively investigates whether immunosuppressive agents on top of heart failure therapy according to current guidelines improves cardiac function and long-term outcome in patients with infl-CMP. Methods and Results: Within the Innsbruck and Maastricht Cardiomyopathy Registry, a total of 209 patients fulfilled the criteria for infl-CMP using endomyocardial biopsy (≥14 infiltrating inflammatory cells/mm 2 ). A total of 110 (53%) patients received immunosuppressive therapy and 99 (47%) did not. To correct for potential selection bias, 1:1 propensity score matching was used on all significant baseline parameters, resulting in a total of 90 patients per group. Baseline characteristics did not significantly differ between both patient groups, reflecting optimal propensity score matching. After a median follow-up of 31 (15–47) months, immunosuppressive therapy resulted in an improved long-term outcome (eg, heart transplantation–free survival) as compared with standard heart failure therapy alone (Log-rank P =0.043; hazard ratio, 0.34 [95% CI, 0.17–0.92]) and in a significant larger increase of left ventricular ejection fraction after a mean of 12 months follow-up, as compared with patients receiving standard heart failure treatment only (12.2% versus 7.3%, respectively; P =0.036). Conclusions: To conclude, this study suggests that immunosuppressive therapy in infl-CMP patients results in an improved heart transplantation–free survival as compared with standard heart failure therapy alone, underscoring the urgent need for a large prospective multicenter trial. Abstract : Supplemental Digital Content is available in the text.